Development of Cheerful Interactive Multimedia (MIC) in Science Subjects for Class V SD KIP V Bara-Baraya Makassar City. - Nurfikriani Eka Putri; Suarlin Suarlin; Andi Makkasau (Universitas Negeri Makassar, 2026)
The goal of this research is to determine whether cheerful interactive multimedia (MIC) can be used in science classes for fifth-grade students at KIP V Bara-Baraya elementary school, Makassar City. This research develops products based on the results of an analysis of student needs using research and development (R&D) types. The research subjects were 20 students in class 5A, and the research and development procedure used was the Alessi & Trollip development model, which began with the planning stage, the design stage, and the development stage. Products developed through additional research go through two stages of testing: alpha and beta. The alpha test or validity test in this study involved two validators, namely the material expert validator and the media expert validator. Based on the results of the media expert validation analysis, an overall score of 93 was obtained with a percentage of 83.03%, so multimedia products are in the